KELAYAKAN BAHAN AJAR IPA INTERAKTIF BERBANTUAN ARTICULATE STORYLINE DALAM MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS IV SD - Tri Utami, Vera; Rokhman, Fathur; Eko Pramono, Suwito; Joko Raharjo, Tri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the effectiveness of interactive science instructional materials assisted by Articulate Storyline in improving fourth-grade elementary students’ conceptual understanding. The study employed a Research and Development approach with a quasi-experimental design involving an experimental class and a control class. The subjects of the study were fourth-grade elementary school students divided into an experimental class that used interactive instructional materials and a control class that used conventional learning materials. Data were collected through conceptual understanding tests administered as pretests and posttests. Data analysis included normality tests, homogeneity tests, independent sample t-tests, and N-Gain analysis. The results indicate a significant difference in students’ conceptual understanding between the experimental and control classes. The experimental class showed a higher posttest mean score and a moderate N-Gain value compared to the control class. These findings demonstrate that interactive science instructional materials assisted by Articulate Storyline are effective in enhancing students’ conceptual understanding. Therefore, such instructional materials can be used as an alternative learning resource to improve science learning outcomes in elementary schools.